Methodological concerns in the study of personal epistemology : the effect of the directness, domain, and open versus closed-ended formats of questions eliciting epistemological assumptions. - Pope, Kathryn J. (My University, 2009)
The study of personal epistemology is concerned with people‟s beliefs or assumptions about the nature of knowledge and knowing, otherwise referred to as epistemological assumptions. As a relatively new field of enquiry, questions about the nature and scope of the construct and how best to investigate it have been tackled by many researchers although fundamental questions still remain. The current study explored the possible effects of three characterisations of questions aimed at eliciting epistemological assumptions on conclusions drawn about such assumptions in terms of their level of sophistication. The three characterisations explored were the level of directness with which questions targeted epistemological assumptions, the domain-specificity of the question, and whether the questions were open or closed-ended. A paper-and-pencil measure was designed to manipulate these variables, and the conclusions drawn about the assumptions of a sample of 30 postgraduate Psychology students were compared across the conditions to determine if there was any evidence for their influence. Comparison of results suggested that the characterisations do exert an influence and caution is raised regarding the validity of methodologies that have been, and continue to be, employed in the study of personal epistemology. The findings further lend support to particular conceptualisations of the construct, but at the same time also unearth additional questions about how epistemological beliefs are best construed and studied.
Keywords: Personal epistemology; Epistemological assumptions; Research; Methodology